High‐dose steroid therapy in BK viremia adversely affected the long‐term graft function after kidney transplantation. Issue 6 (20th October 2016) - Kim, Hyosang; Yu, Hoon; Baek, Chung Hee; Han, Duck Jong; Park, Su‐Kil
Abstract: Background: Although high‐dose steroid therapy has been attempted for the management of clinically suspected allograft rejection, before testing for BK viral activity or acute cellular rejection accompanied by BK polyomavirus nephropathy, its long‐term outcome remains unknown. We investigated the impact of high‐dose steroids on BK viral activity and long‐term graft outcomes in patients with BK viremia. Methods: The study population comprised 144 kidney transplant recipients with BK viremia. They were divided into 2 groups based on the amount of steroids administered: low‐dose group (<2 g, n =123) or high‐dose group (≥2 g, n =21). Results: The baseline serum BK viral loads were 5.4±1.1 log cp/mL in the low‐dose group and 6.0±1.3 in the high‐dose group ( P =.054). These changed to 5.2±1.3 and 6.1±1.4, 1 month after steroid treatment ( P =.03) and 4.9±1.3 and 5.9±1.4 at 2 months ( P =.033), respectively. From 3 months to 1 year, the serum BK viral titers were not different between groups. Kaplan‐Meier analyses demonstrated that the rates of the decline of graft function and graft failure were higher in the high‐dose group ( P =.02 and P =.04, respectively). High‐dose steroids ( P =.012, hazard ratio [HR] 5.04, 95% confidence interval [CI] 1.42–17.85) and log serum BK viral load at 2 months after steroid treatment ( P =.042, HR 1.52, 95% CI 1.02–2.28) were independent risk factors for the decline of graft function. Conclusion: High‐dose steroids induced BK viral activation and subsequently resulted in poor long‐term graft function and early graft failure in patients with BK viremia.